Hubungan Beberapa Faktor dengan Kehamilan Tidak Diinginkan di Indonesia Tahun 2017 (Analisis Data Sekunder SDKI Tahun 2017) - Nisa, Rofifatun; Mawarni, Atik; Winarni, Sri (Jurnal Riset Kesehatan Masyarakat, 2021)
The unwanted pregnancy rate in Indonesia reached 15 percent (7% unwanted pregnancy and 8% mistimed pregnancy) in 2017. Unwanted pregnancy have an impact on increasing the risk of maternal mortality  (305 per 100.000 population) and  infants mortality (24 per 1.000 live births)   in Indonesia, that these rates are  still relatively high. This research aims to determine the relationship of several factors with unwanted pregnancy. This research is a quantitative with a cross sectional design using secondary data from the 207 IDHS. The sample used is pregnant women in Indonesia based on the 207 IDHS data as many as 1.996 respondents. Statistical analysis used chi-square test. The result showed that the highest of unwanted pregnancy occured in pregnant women who worked (3,9%), had a history of non-ideal parity or more than two children (11,1%), had used contraception (5,1%), and are breastfeeding (13,9%). Unwanted pregnancy occured equally in respondents with good and poor knowledge of reproductive health, respectively 3,7%. Chi-square analysis showed that the factors that were significantly associated with unwanted pregnancy were history of parity (p = 0,0001; OR = 18,97; 95%CI = 9,33-38,58), history of contraceptive use (p = 0,0001; OR = 5,29; 95%CI = 2,36-11,86), and breastfeeding behavior (p= 0,005; OR= 0,23; 95%CI = 0,09-0,63). The factors that were not significantly related were employment status (p = 0,804; OR = 0,904; 95%CI = 0,56-1,46 ) and knowledge of reproductive health (p = 1,0; OR = 0,012; 95%CI = 0,53-1,94). The conclusion of this study is  history of parity, history of contraceptive use, and breastfeeding behavior are factors associated with unwanted pregnancy.